PROTOZOOLOGICAL EXAMINATION OF THE BLOOD OF SOME MEXICAN BIRDS - BELTRAN, ENRIQUE (INSTITUTO MEXICANO DE RECURSOS NATURALES RENOVABLES, 1940)
Some 17 vars of chillies (Capsicum annuum) showed an ascorbic acid content of 174 to 1848 mg per g of fresh product The content was approx inversely proportional to the capsaicine content In any given var the outer portions contain more ascorbic
CIENC MEX
Keywords: PROTOZOOLOGICAL EXAMINATION, BLOOD, MEXICAN BIRDS; MULTIDISCIPLINARIA; CIENCIAS VETERINARIAS; PATOLOGIA